2022
DOI: 10.1109/access.2022.3190608
|View full text |Cite
|
Sign up to set email alerts
|

Novel Micro-LED Display Featuring Fingerprint Recognition Without Additional Sensors

Abstract: This paper proposes a new architecture for a micro light emitting diode (micro-LED) display featuring fingerprint detection without any additional light emitting and sensing devices in mobile applications. This paper proposes that conventional LEDs can be used as photodetectors in active-matrix pixel circuits. In the area where a finger touched, some LEDs are used as photodetectors and others are used as light emitting sources. The photocurrents of reverse-biased LEDs under various illumination conditions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…On top of the main function to display images on the screen, more efforts have made good progress on integrating additional functions in display panels such as image sensing [146][147][148], fingerprint sensing [149][150][151][152][153][154], temperature sensing [155][156][157][158][159], visible light communication [160][161][162][163], and actuators for haptic applications [164]. To support these diverse functions as well as the display scanning, the demands for the higher flexibility in gate driver circuits is going to increase.…”
Section: Discussionmentioning
confidence: 99%
“…On top of the main function to display images on the screen, more efforts have made good progress on integrating additional functions in display panels such as image sensing [146][147][148], fingerprint sensing [149][150][151][152][153][154], temperature sensing [155][156][157][158][159], visible light communication [160][161][162][163], and actuators for haptic applications [164]. To support these diverse functions as well as the display scanning, the demands for the higher flexibility in gate driver circuits is going to increase.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse-biased LEDs have photodetecting characteristics, so when lights are irradiated, photocurrents flow through the LEDs. In our previous studies, we proposed pixel circuits using TFTs and verified that AMLED displays are capable of photodetection [4,5]. In this study, we introduce a pixel driver IC (PDIC) that can drive RGB LEDs and propose a sensing circuit for light detection.…”
Section: Introductionmentioning
confidence: 91%
“…This is in contrast to other existing longitudinal FP datasets, which range in length from minutes to up to 30 years. In [12] A novel design was put forth for a micro-LED display that can identify fingerprints without the need for extra sensors. The system confirmed that the active-matrix pixel circuits may employ regular LEDs as photo detectors.…”
Section: IImentioning
confidence: 99%